774 Operative Experience Targets in General Surgery Training: A Systematic Review. (19th August 2022) - Toale, C; O'Byrne, A; Morris, M; O Kavanagh, D
Abstract: Aim: Operative experience targets are well established as a proxy measure for operative competence in surgical training across jurisdictions. The aim of this study was to examine the validity evidence of operative experience targets in surgical training as an assessment tool. Method: A systematic review of the PubMed, EMBASE, Web of Science and Cochrane library databases was conducted in accordance with the PRISMA guidelines. The educational impact of included studies was evaluated using a modified Kirkpatrick model. Results: Of 3, 672 records identified on database searching, 11 papers were ultimately included in a narrative synthesis. Two studies reported a positive relationship between operative experience and self-reported confidence only (Kirkpatrick level 2a). Six studies documented improvements in assessed trainee performance associated with experience (Kirkpatrick level 2b). No study documented trainee behavioural change, or changes in organisational practice, related to experience targets (Kirkpatrick level 3 and 4a). No studies have identified an association between trainees reaching mandated experience targets and improved clinical outcomes. Conclusions: Definitive evidence comparing either clinical or assessment outcomes for trainees who have reached pre-defined experience targets compared to those who have not is lacking. A number of studies have recorded competent trainee performance in key index procedures only after reaching experience thresholds greatly in excess of currently mandated targets in Ireland and the United Kingdom. This review supports the move away from these targets toward objective assessor-mediated measures of trainee competence.